FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT JUDGEMENT DI KANTOR AKUNTAN PUBLIK KOTA SURABAYA - Putra, R. Rendra Okta Pratama; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to analyze (a) the influence of audit experience to the audit judgment; (b) the influence of obedience pressure to the audit judgment; (c) the influence of tasks complexity to the audit judgment; (d) the influence of skepticism of professional auditor to the audit judgment; (e) the influence of locus of control to the audit judgment. The respondents are all auditor staffs (manager, partner, senior, and junior auditor) on Public Accountant Firm (PAF) in Surabaya. The sample collection has been carried out by using causative method. This research has been carried out by using multiple linear regressions analysis model. It has been found from the result of the analysis that audit experience has positive and significant influence to the audit judgment. Obedience pressure has negative and significant influence to the audit judgment. Tasks complexity has positive and significant influence to the audit judgment. The skepticism of professional auditor has positive and significant influence to the audit judgment. The locus of control has negative and insignificant influence to the audit judgment.Keywords: Audit experience, obedience pressure, tasks complexity, skepticism of professional audit, locus of control, audit judgement.